1998
DOI: 10.1111/j.1751-1097.1998.tb05293.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Photodynamic Therapy on Human Neutrophil Migration Using Bacteriochlorin a

Abstract: Bacteriochlorin a photodynamic therapy (BCA-PDT) caused inhibition of interleukin (IL)-8-activated neutrophil migration, at concentrations that did not induce membrane damage. Random migration and migration induced by other chemoattractants were also inhibited, indicating that the effect of BCA-PDT was not at the level of chemoattractant-receptor interaction but down stream. The BCA-PDT completely blocked superoxide production of phorbol ester-stimulated neutrophils indicating that superoxide production by neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
(5 reference statements)
1
13
0
Order By: Relevance
“…In the case of tumors, the response to PDT is thought to be caused by a combination of direct cytotoxicity and vascular occlusion, which leads to tumor ischemia (36). Inflammatory reactions are also very important, because they give rise to neutrophil infiltration, which itself participates in tumor cell eradication (30). In these last two situations, endothelial cells play a pivotal role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of tumors, the response to PDT is thought to be caused by a combination of direct cytotoxicity and vascular occlusion, which leads to tumor ischemia (36). Inflammatory reactions are also very important, because they give rise to neutrophil infiltration, which itself participates in tumor cell eradication (30). In these last two situations, endothelial cells play a pivotal role.…”
Section: Discussionmentioning
confidence: 99%
“…genes encoding chemokines. These genes were chosen because neutrophil recruitment was reported post-PDT (30). As shown in Fig.…”
Section: Nf-b Is Activated In Endothelial and Colon Cancer Cells By Pmentioning
confidence: 99%
“…BCA can be an effective PDT that induces death of cancer cells; it has also been applied for locating tumor tissues both in vitro and in vivo . Therefore, we attempted to determine a specific enzyme that can obtain BChlide a, which could be produced directly by degrading BChl a. BChl a is similar to Chls that can perform a unique light‐capturing errand for photosynthesis in photosynthetic bacteria .…”
Section: Discussionmentioning
confidence: 99%
“…However, the physical and chemical properties of Photofrin II™ restrict its applicability; thus, current studies have focused on developing new photosensitizers. Previous studies have reported that bacteriochlorin a (BCA) is a favorable photosensitizer candidate for both in vitro and in vivo studies, and rarely causes allergic reactions or photosensitizes the skin . WST09 and WST11 are used in clinical evaluations of commercial BCA.…”
Section: Introductionmentioning
confidence: 99%
“…Two BCs recently investigated consist of a BChla-serine complex 8 and a BChl a derivative, BCa, 9 which absorb light in the 760-780 nm region. A considerable effort is now devoted to additional secondgeneration photosensitizers with tailored light-absorption properties such as the purpurins, porphyrins with annelated cyclopentenyl rings which are formally at the saturated level of chlorins and typically absorb light in the 650-715 nm region.…”
Section: Introductionmentioning
confidence: 99%